Triple‐bottom‐line approach for comparing point‐of‐use/point‐of‐entry to centralized water treatment. Issue 2 (3rd March 2023) - Lane, Kaycie; Reckhow, David; Tobiason, John; Kumpel, Emily
Abstract: Small drinking water systems in the United States often suffer from repeated Safe Drinking Water Act water quality violations that necessitate upgrades to the existing centralized systems to achieve compliance. Community water systems (CWSs) need to evaluate the tradeoffs between public health, environmental and economic impacts when choosing these system improvements. This study developed the input and output components of a triple‐bottom‐line methodology to compare two alternatives: (1) installing a centralized treatment upgrade or (2) a point‐of‐use/point‐of‐entry device over a 30‐year period, using a health exposure assessment specific contaminants, life cycle analysis of environmental impacts improvement, and life cycle costing to account for the useful life of components and the number of households served by a CWS. We present recommendations and considerations for future usage of the triple‐bottom‐line approach methodology.